Development of a web-based real estate application at Raya Houses - M Julius Saputra; Desi Ramayanti (FORMAT, 2025)
This research develops a web-based real estate management system to enhance property management efficiency at Raya Houses, Jakarta. The system includes listing management, filter-based property search, AI-generated property articles, popular property analysis based on visits, and automated sales contract generation. A hybrid development approach combines Waterfall for linear structure and Kanban for iterative flexibility. Data were gathered through online observation and agent interviews, followed by functional testing of key features. Testing results show all features function as specified, improving agent operational efficiency and data accuracy. Implemented using Laravel, MySQL, and Docker, this system provides an innovative solution for automating real estate business processes, leveraging AI and document generation features underexplored in prior work.